Enhancing usable appliances for energy integration with solar power - Chandra Debnath, Sumon; Yeasmin, Nilufa; Siddika, Ayesha; Sultana, Munira; Bashar, M S; Rahaman, Mashudur; Islam, Suravi; Tabassum, Samia (Bangladesh Journal of Scientific and Industrial Research, 2023)
Solar energy is one of the prospective sources of Bangladesh which can meet energy demand and provide a contribution to sustainable development goals. Besides the use of the solar system in electricity generation for households, some other sectors are also using photovoltaic in irrigation, street lighting, water pumping, etc. This article introduces the idea of some other applications of solar photovoltaic systems. Here, solar backpack, farm hat, and grass cutter are designed and fabricated to utilize solar energy for recharging storage systems as well as being operated directly in the daylight. Solar powered charging backpack uses a solar panel of 5 W/17 V capacity at the front side of the backpack with a 5 V output voltage which can charge mobile phone or rechargeable battery. The results clearly showed that it is capable to charge the phone and the charging level of mobile phone successfully raised from 22% to 88% within 5 hours by putting it in direct sunlight on cloudy weather. This article also explained solar farm hat which is very simple but effective for our farmers. Light weight solar powered fan (1.92 W/12 V DC) placed on the top of the hat which is used to cool their face. Lighting (4 ultra-bright 3 V LEDs) and battery charging system are also attached in this system. Further, Solar powered grass cutter machine is designed and developed mainly considering the air pollution using fossil fuels which can also be a usable solar energy appliances. These appliances can keep role to build a eco-friendly system. Bangladesh J. Sci. Ind. Res. 58(4), 191-200, 2023